2022
DOI: 10.1177/10600280221140480
|View full text |Cite
|
Sign up to set email alerts
|

Ponesimod: An Oral Second-Generation Selective Sphingosine 1-Phosphate Receptor Modulator for the Treatment of Multiple Sclerosis

Abstract: Objective: To describe the safety, efficacy, and potential role in therapy of ponesimod, which was recently approved by the Food and Drug Administration (FDA) as a therapeutic option for the treatment of multiple sclerosis (MS). Data Sources: A PubMed literature search using the following terms: ponesimod and MS (January 1, 2012-October 31, 2022). FDA product labeling was also reviewed for pertinent data sources. Study Selection and Data Extraction: All relevant English-language articles examining efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 22 , 23 Ponesimod attenuates inflammation, demyelination and axonal loss in the brain and spinal cord of mice with experimental autoimmune encephalomyelitis (EAE), an animal model for MS. 24 Recently, Ponesimod has been approved by the FDA for MS therapy. 25 Tissue distribution studies show that Ponesimod can penetrate the blood–brain-barrier and partition to the brain and spinal cord. 19 , 26 These studies indicate that, in addition to preventing access of lymphocytes to the CNS, Ponesimod may have also direct effects on neuroprotection and anti-neuroinflammation via downregulating S1PR1 cell signaling pathways in neural cells.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Ponesimod attenuates inflammation, demyelination and axonal loss in the brain and spinal cord of mice with experimental autoimmune encephalomyelitis (EAE), an animal model for MS. 24 Recently, Ponesimod has been approved by the FDA for MS therapy. 25 Tissue distribution studies show that Ponesimod can penetrate the blood–brain-barrier and partition to the brain and spinal cord. 19 , 26 These studies indicate that, in addition to preventing access of lymphocytes to the CNS, Ponesimod may have also direct effects on neuroprotection and anti-neuroinflammation via downregulating S1PR1 cell signaling pathways in neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody drugs against S1P have also been developed and are currently in clinical development [ 183 , 215 ]. A number of molecularly targeted drugs that act more specifically on S1P receptors have been developed and are being tested in clinical trials as potential treatments for multiple sclerosis and inflammatory bowel disease [ 226 , 227 , 228 , 229 ].…”
Section: Targeting S1p As Therapy For Advanced Breast Cancermentioning
confidence: 99%
“…Therefore, the development of therapies targeting S1P signaling requires the selection of target patient groups, the development of S1P signaling inhibitors, and consideration of combination therapy with anti-cancer drugs and molecular-targeted drugs. A variety of agents have been developed to regulate S1P signaling, each with different targets, and clinical development strategies must be tailored to the pathophysiology of the cancer [ 181 , 226 , 227 , 228 , 229 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 ]. S1P signaling inhibitors developed to date, which could be applied to cancer therapy, are listed in Table 1 .…”
Section: Targeting S1p As Therapy For Advanced Breast Cancermentioning
confidence: 99%
“…Myśliwiec et al [69] also suggested that S1P is an intermediate link between psoriasis and multiple metabolic-related diseases. Since S1P signaling is involved in multiple immune functions, targeted S1P therapeutics have been clinically validated for a variety of immune diseases, such as nonalcoholic fatty liver disease (NAFLD), multiple sclerosis (MS), ischemic stroke, and coronary artery disease [70][71][72][73]. In the last decade, the role of S1P and its signaling in recalcitrant skin diseases has also been elucidated.…”
Section: S1p and S1pr Modulators For The Treatment Of Psoriasismentioning
confidence: 99%